Natural space and pilgrimages in Medjugorje - Belaj, Marijana (2014)
One of the most important specificity of Medjugorje are apparitions of Virgin Mary which, as visionaries testify, have been going on for more than 30 years. Testimonies about the apparitions have activated millions of pilgrims from all over the world and thus thoroughly changed the primary demographic, economic and urban face of Medjugorje. However, from the beginning of the pilgrimage history of Medjugorje to date, the alleged apparitions of Mary and pilgrimage itineraries have been inseparable from the authentic rough and avaricious Medjugorje karst. Unlike most famous pilgrimage destinations that are located on the sites of exceptional geographic beauty (Morinis), the space of Medjugorje is rather characterized by the rugged land. Nevertheless, pilgrims find it attractive. As reported, steep and rocky slopes evoke in pilgrims a sense of peace, spiritual inspiration and creativity, and become a part of their experience. This presentation deals with the interaction between natural space and pilgrimage concepts and experiences. It analyses what spiritual magnetism (Preston) the landscape of Medjugorje holds for pilgrims, and how sacred values are created and inscribed in natural environment. At the same time, it discusses how this sacralized landscape shapes pilgrims' experiences, thus becoming a place of personal transformation. These questions will be considered through spatial, material and discursive practices of pilgrims and other agents who create and use the pilgrims' Medjugorje.
ENG